Bisnis Dan Kewirausahaan Syariah: Prinsip, Konsep, Dan Implementasi Dalam Ekonomi Modern - Lismawati Lismawati; Muhammad Zakir; Mohd Winario (EL-EMIR Institute, 2026)
This article examines the concept of business and entrepreneurship from the perspective of Islamic economics as an alternative economic system based on Islamic values. This research uses a descriptive-analytical approach to outline the basic principles of Islamic business, such as the prohibition of riba (usury), gharar (gharar), and maisir (gambling), as well as the application of justice, transparency, and social responsibility in economic activities. Furthermore, this article discusses the characteristics of Muslim entrepreneurs, who are oriented not only toward profit but also toward blessings, ethics, and contributions to the welfare of the community. The study's findings indicate that Islamic business has the advantage of creating a balance between economic and social goals, thereby promoting sustainable societal welfare. In the modern economic context, the implementation of Islamic entrepreneurship faces various challenges, such as low Islamic financial literacy, limited access to capital, and global market competition. However, significant opportunities exist through regulatory support, the development of digital technology, and increasing public awareness of halal products. Therefore, strategies are needed to strengthen an innovative, inclusive, and highly competitive Islamic business ecosystem.